Original paperExamining proprioception in the knee joint area of patients suffering from lumbar spine discopathy - Gasik, Robert; Styczyński, Tadeusz; Pyskło, Bohdan (Reumatologia/Rheumatology, 2007)
Lumbar spine hernial discopathy may cause neurological deficits. The study objective was to evaluate proprioception dysfunctions in knee joints of patients with damage of nerve roots in the course of lumbar spine hernial discopathy. The study material included 54 patients at the average age of 50.4 years. Sciatic neuralgia symptoms of long lasting nature were revealed among all examined patients. The patients were physically examined. Muscle force repeatability measurements of knee joints were performed by using a dynamometric measuring station. Vibration perception was measured in sclerotomes L3, L4, L5, S1. They revealed force repeatability impairments of flexor muscles (among 72.2% of patients) and extensor muscles (among 79.6% of patients) of knee joints on the side of radicular syndrome in comparison with the opposite limb. Vibration perception disorders on the side of radicular syndrome were revealed in 40.7% of the examined patients. Vibration perception level on the healthy side was also statistically considerably lower in comparison with the standards. The obtained results indicate proprioception impairment among patients with damage of nerve roots in the course of lumbar spine hernial discopathy. Presence of proprioception impairment in the lower limb, without damage of nerve roots, requires further examination and observation. One cannot exclude that perception level among patients with lumbar spine discopathy is primarily lower than the average level.